Human Myocardium Has a Robust α1A-Subtype Adrenergic Receptor Inotropic Response. Issue 3 (September 2018) - Janssen, Paul M. L.; Canan, Benjamin D.; Kilic, Ahmet; Whitson, Bryan A.; Baker, Anthony J.
Abstract : Abstract: Recent studies report that a single subtype of α1-adrenergic receptor (α1-AR), the α1A-subtype, mediates robust cardioprotective effects in multiple experimental models of heart failure, suggesting that the α1A-subtype is a potential therapeutic target for an agonist to treat heart failure. Moreover, we recently found that the α1A-subtype is present in human heart. The goal of this study was to assess the inotropic response mediated by the α1A-subtype in human myocardium, and to determine whether the response is downregulated in myocardium from failing human heart. We measured in vitro contractile responses of cardiac muscle preparations (trabeculae) isolated from the right ventricle from nonfailing and failing human hearts. Addition of the α1A-subtype agonist A61603 (100 nM) resulted in a large positive inotropic response (force increased ≈ 2-fold). This response represented ≈70% of the response mediated by the β-adrenergic receptor agonist isoproterenol (1 μM). Moreover, in myocardium from failing hearts, α1A-subtype responses remained robust, and only slightly reduced relative to nonfailing hearts. We conclude that α1A-subtype–mediated inotropy could represent a significant source of inotropic support in the human heart. Furthermore, the α1A-subtype remains functional in myocardium from failing human hearts and thus, might be a therapeutic target to support cardioprotective effects in patients with heart failure.